Comparison of Anti-Inflammatory Activity between Fermented and Dried Breadfruit Leaves Extract - Hesti Riasari; Sani N. Fitriansyah; Oktamuman Putra (Universitas Padjadjaran, Indonesia)
Breadfruit leaves (Artocarpus altilis) have been empirically used to treat inflammation. Biosynthesis process such as fermentation can possibly changes the composition of secondary metabolites in breadfruit leaves. The aim of this study was to compare the anti-inflammatory activity between fermented and natural-dried breadfruit leaves extract. Fermented and dried breadfruit leaves were extracted with soxhlet device using methanol solvent. The anti-inflammatory activity of both extracts were evaluated using carrageenan (1% w/v) foot edema model of inflammation in male Wistar rats. The edema was measured with plethysmometer every 1 hour for 6 hours. The results showed that both extracts exhibited anti-inflammatory activity. 50 mg and 100 mg fermented leaves extracts exhibited 37.17% and 71.82% inhibition, while the same concentrations of dried extract exhibited 39.50% and 57.72%, inhibiton respectively. In conclusion, the best anti-inflammatory activity was shown by fermented breadfruit leaves extract.Keywords: Artocarpus altilis, anti-inflammatory, breadfruit, fermentation